PENGARUH DIGITAL MARKETING, KUALITAS PRODUK DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KERUPUK IKAN TAMBAN ADAM SNACK KAMPUNG JAWA KABUPATEN BINTAN - Cindi Anggraeni; Bunga Paramita; Sufnirayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of digital marketing, product quality, and product innovation on the purchasing decisions of Adam Snack tamban fish crackers in Kampung Jawa, Bintan Regency. The study employed a quantitative approach using a survey method through questionnaires distributed to 100 respondents who were consumers of Adam Snack tamban fish crackers in Bintan Regency. The data were analyzed using multiple linear regression analysis with the assistance of IBM SPSS version 26 software. The results showed that simultaneously, the three independent variables (digital marketing, product quality, and product innovation) had a significant effect on purchasing decisions, with an Adjusted R Square value of 0.639, indicating that 63.9% of the variation in purchasing decisions could be explained by the combination of these three variables, while the remaining 36.1% was influenced by other factors not examined in this study. However, partially, digital marketing and product innovation had a significant effect on purchasing decisions, whereas product quality did not show a significant effect. This indicates that product innovation, such as variations in size, shape, and attractive packaging, became the main factor influencing consumer purchasing decisions, supported by digital marketing strategies that were able to expand product information and promotion to consumers. This study contributes to business actors by showing that improving purchasing decisions can be optimized through strengthening digital marketing strategies and continuously developing product innovation.